1978
DOI: 10.1002/ana.410030508
|View full text |Cite
|
Sign up to set email alerts
|

Infantile spasms in down syndrome: A report of 5 cases and review of the literature

Abstract: Five patients with Down syndrome (DS) and infantile spasms were examined in a four-year interval. Previous reports of this association have been infrequent except during experimental treatment with 5-hydroxytryptophan, a precursor of serotonin. Malformations of the brain in DS are associated with an increased incidence of epilepsy, and both gross and cytoarchitectural anomalies have been described. The severity and distribution of these central nervous system anomalies presumably predispose to the infantile sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
2
1

Year Published

1982
1982
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 7 publications
1
34
2
1
Order By: Relevance
“…Of those with epilepsy, reflex epilepsies (210) and infantile spasms (211,212) are most common. In recent times, a second increase in the prevalence of epilepsy (9-10%) has been reported after age 50 years, associated with dementia (213,215).…”
Section: Chromosome 21mentioning
confidence: 99%
“…Of those with epilepsy, reflex epilepsies (210) and infantile spasms (211,212) are most common. In recent times, a second increase in the prevalence of epilepsy (9-10%) has been reported after age 50 years, associated with dementia (213,215).…”
Section: Chromosome 21mentioning
confidence: 99%
“…The incidence of epilepsy in children with DS was estimated to be 1.4% (Tat-sun0 et al, 1984) and was considered to be not much higher than in the general population. It has been observed that infantile spasms have a high incidence in DS (Pollack et al, 1978; Tatsuno et al, 1984), that febrile convulsions are less common in DS patients than in the general population (Tatsuno et al, 1984) and that the overall prevalence of epilepsy increases with age in DS beyond the prevalence in the general population, reaching 12.2% in patients over 35 (veall, 1974).…”
mentioning
confidence: 99%
“…Infantile spasms, particularly frequent in male patients, are usually associated with a poor long-term prognosis (Fig. 1) [19,51,62-65]. However about half of the children with infantile spasms achieve seizure remission without relapse and partial restoration of development.…”
Section: Resultsmentioning
confidence: 99%